(untitled) (Bangladesh Journal of Medical Science, 2025)
This scoping review explores the landscape of social entrepreneurship initiatives targeting period poverty, a pressing issue affecting millions of individuals worldwide. The evaluation identifies diverse strategies social enterprises employ by systematically mapping existing programs, including producing and distributing affordable menstrual hygiene products, educational outreach on menstrual health, and community engagement initiatives. Through a comprehensive analysis of reported outcomes, this study highlights successful models and challenges entrepreneurs face in this field. Furthermore, it reveals significant gaps in the current literature, suggesting critical areas for future research and intervention. The findings aim to inform practitioners, policymakers, and researchers about effective approaches to combat period poverty. Ultimately, this review seeks to advocate for sustainable solutions that empower individuals and promote gender equity. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 33-50